BISNIS PEMBUATAN KAROSERI DUMP TRUCK PADA PERUSAHAAN MAIWA KAROSERI - Gunawan, Erik; Arifin, Zaenal; Sobirin, Achmad (ITB AAS Indonesia Surakarta, 2024)
The business in the truck body manufacturing sector is one of the potential business sectors, especially in the North Luwu area, where this area has a lot of agricultural commodities that require transportation equipment such as trucks in the business process. This business practice is carried out to find out the strategy for creating SKRB ownership, cost leadership strategy, and differentiation strategy in winning the competition. This business is carried out in the North Luwu area and has been running for about a year. Based on the results of business practices that have been passed, the results show that the SKRB ownership strategy and cost leadership strategy are not an advantage or a competitive advantage in winning the competition. Meanwhile, a differentiation strategy in which the company makes one product with excellent strength and very smooth results becomes a competitive advantage. Unfortunately, this differentiation strategy has the effect of expensive product prices, causing body sales to not meet expectations. Keywords : dump truck carosery, business, strategies